u-61=1

Simple and best practice solution for u-61=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for u-61=1 equation:



u-61=1
We move all terms to the left:
u-61-(1)=0
We add all the numbers together, and all the variables
u-62=0
We move all terms containing u to the left, all other terms to the right
u=62

See similar equations:

| 6(2x+12)=96 | | 91.90=14.7v+47.8 | | 5(x+4)=6x-24 | | c-149=586 | | 6s=30 | | -2(11-7x)+54=4 | | z+18=60 | | -84=7(b-6) | | 72.50=46.9a+25.6 | | 49+29=w | | h+3=74 | | c-5=18 | | 16-r.7=21 | | 3x+4x+7x=42 | | 48.7=8.1p+0.1 | | p=42-20 | | 4x+6=-2x-30 | | 10.40=d+0.9 | | j-37=48 | | -15(u–5)=15 | | 30.7=4.5s+26.2 | | 2^6x-5×2^3x+4=0 | | (9/2z)+(4/5)=-2 | | h=24/6 | | (Y•y)+y+30=180 | | 4(1x-4)=1x+14 | | 3×+y=1 | | 76=19w | | 2^6-5×2^3x+4=0 | | 2x(x+6)+4=10+4x | | 4(2t+8)=88 | | 9.7=-3.7h+13.4 |

Equations solver categories